1993
DOI: 10.2307/2947233
|View full text |Cite
|
Sign up to set email alerts
|

Legal History of the Colonial South: Assessment and Suggestions

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. T X SHE court and the law were at the very center of life in the colonial South. Rhys Isaac and A. G. Roeber argue that the county courts in Virginia were arenas in which lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Either way, his and Gordon's comments suggest that attendance during colonial Virginia court days is another legal issue about which historians assume much and know little. Despite repeated scholarly calls for close quantitative examination of legal procedures generally, many court functions remain mysterious (Henretta and Rice 1993;Konig 1993;Snyder 1993).…”
mentioning
confidence: 99%
“…Either way, his and Gordon's comments suggest that attendance during colonial Virginia court days is another legal issue about which historians assume much and know little. Despite repeated scholarly calls for close quantitative examination of legal procedures generally, many court functions remain mysterious (Henretta and Rice 1993;Konig 1993;Snyder 1993).…”
mentioning
confidence: 99%
“…It was perhaps the wealthiest planters and merchants who best exemplified the creation of authority by transforming their economic success into social and political influence. Terri Snyder maintains that Southern planters used the law “to fashion an economy of slavery that served their needs and to shape a distinct social structure”; she and other legal historians have demonstrated that in the mainland's southern colonies “law reinforced the interests of the dominant class.”…”
mentioning
confidence: 99%
“…In particular, see Suzanne Desan (2004) 2. See Snyder (1993). Snyder suggested that such will studies might contribute much to Southern history.…”
mentioning
confidence: 99%